World Development Report 2014 : Risk and Opportunity—Managing Risk for Development - World Bank (Washington, DC, 2013)
The past 25 years have witnessed unprecedented changes around the world—many of them for the better. Across the continents, many countries have embarked on a path of international integration, economic reform, technological modernization, and democratic participation. As a result, economies that had been stagnant for decades are growing, people whose families had suffered deprivation for generations are escaping poverty, and hundreds of millions are enjoying the benefits of improved living standards and scientific and cultural sharing across nations.